(-2x^3y^4z^2)(-3x^2y^3z)^3

(-2x^3y^4z^2)(-3x^2y^3z)^3 = (-2x^3y^4z^2)(-27x^6y^9z^3) = 54x^9y^13z^5

Question

Asked 5/3/2015 2:16:57 PM

Updated 5/14/2015 12:24:39 PM

1 Answer/Comment

s

Rating

8

(-2x^3y^4z^2)(-3x^2y^3z)^3

= (-2x^3y^4z^2)(-27x^6y^9z^3)

= 54x^9y^13z^5

= (-2x^3y^4z^2)(-27x^6y^9z^3)

= 54x^9y^13z^5

Added 5/14/2015 12:24:39 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [5/15/2015 3:22:28 AM]

z^8 / z^-4

Question

Updated 8/17/2018 10:02:52 AM

1 Answer/Comment

z^8 / z^-4

= z^8-(-4)

= z^12

= z^8-(-4)

= z^12

Added 8/17/2018 10:02:52 AM

This answer has been confirmed as correct and helpful.

34,567,069

questions answered

There are no comments.